Treatment of set order relations by means of a nonlinear scalarization functional: a full characterization. (2nd October 2016) - Köbis, Elisabeth; Köbis, Markus A.
Abstract : In this paper, we show how a nonlinear scalarization functional can be used in order to characterize several well-known set order relations and which thus plays a key role in set optimization. By means of this functional, we derive characterizations for minimal elements of set-valued optimization problems using a set approach. Our methods do not rely on any convexity assumptions on the considered sets. Furthermore, we develop a derivative-free descent method for set optimization problems without convexity assumptions to verify the usefulness of our results.